Effectiveness of interventions to improve participation outcomes for children with developmental coordination disorder: A systematic review. (April 2020) - O'Dea, Áine; Robinson, Katie; Coote, Susan
Introduction: Developmental coordination disorder affects a child's motor abilities and participation across environments. This study aimed to review systematically the effectiveness of interventions using a motor, cognitive or psychological approach on participation outcomes in children with developmental coordination disorder. Method: A systematic review of the literature published between 2001 and November 2017 was conducted. Eight electronic databases were searched: Embase, PubMed, CINAHL, PsycINFO, the Cochrane Library, Education Full Text (H. W. Wilson databases), SPORTDiscus (all via EBSCO) and Scopus (Web of Science). Results: In total, 12 studies met the inclusion criteria: seven randomised controlled trials, two quasi-experimental and three case series. Systematic quality assessment and meta-analysis was not possible given the heterogeneity of research designs, interventions and outcome measures. Limited evidence for participation outcomes was found. The cognitive orientation to daily occupational performance intervention found a between-group effect on the Canadian Occupational Performance Measure (COPM) outcome measure performance, g = 1.0 (0.02, 1.9), and COPM satisfaction, g = 1.4 (0.4, 2.3), in favour of the cognitive orientation to daily occupational performance for one randomised controlled trial. Large significant within-group effects were found for the cognitive orientation to daily occupational performance intervention on the COPM outcome measure COPM satisfaction, d = –2.1 (–5.2, –0.2). Conclusion: More high-quality research is needed to strengthen the evidence base regarding occupational therapy interventions to improve participation outcomes for children with developmental coordination disorder.